Effect of different cooling methods on the corrosion behaviour at welded area of aluminium alloy. (1st March 2014) - Wan Nik, W.; Rosliza, R.; Zulkifli, M.; Hui, D.
Abstract : The effect of different cooling methods on the corrosion behaviour at welded area of aluminium alloy 5083 was investigated by using weight loss study, potendynamic polarization study and morphology study. All samples were cooled by using air cooling method and quenching method. There was an increase of weight loss for both cooling methods where samples with air cooling method showed lower percentage of weight loss as compared to samples with quenching methods. The corrosion rate gained from this study revealed that samples with air cooling method showed lower corrosion rate compared to samples with quenching method. In potentiodynamic polarization study, the value of corrosion current density, Icorr increased with respect to immersion period. This behaviour signifies the occurrence of porosity where the air cooled samples show lower value of Icorr compared to quenched samples. The increase in Icorr causes the value of polarization resistance, Rp to decrease and corrosion rate to increase. The morphology study conducted revealed the existence of porosity and caused pitting corrosion on quenched samples which proved the samples with quenching method was more corroded as compared to samples with air cooling method.